(untitled) (HIMALAYA, 2019)
Although the first road to ever be built into Humla, Nepal is still under construction, it has already spurred numerous sociocultural and economic changes, including an increased integration into the market economy, changing access to market-purchased foods, and new kinds of health-seeking behavior. This paper is part of a larger research project where we examined changing health and nutrition outcomes co-synchronous with the arrival of this road. In this paper, we focus on whether and how the road is affecting villagers’ subjective well-being (SWB). We studied this while living and working with people from two Humli villages, one that is on the road, and one that is far from it. In these villages, we developed two local models of SWB, using the villagers’ own conceptual frameworks and sense of the factors that play a role in wellbeing. Our analyses showed that villagers’ conceptualization of SWB varied substantially according to road proximity. Additionally, we quantified indices from villagers’ SWB assessments and tested which variables were significant determinants of wellbeing. We discovered a significant relationship between an individual’s well-being level and two variables: available resources per household and levels of social support. The purpose of this paper is threefold: to better understand how villagers from Upper Humla define SWB, to identify which subset of the population is not benefitting in terms of their SWB from the new road, and to present a mixed-methods, anthropologically-based approach for the development of a locally meaningful measure of SWB.